FILOSOFI MULTIKULTURALISME DALAM PENDIDIKAN MUSIK - Djohan Salim (FBS UNY, 2006)
In these recent years, the issue of multiculturalism cannot be ignored in education. It has become a topic of discussions in various settings, such as academic and non-academic forums, political debates, cultural studies, and popular news. The aim of this article is to answer questions about what multiculturalism is and what it means to educators, especially those in music education. Support to music educators in all levels to understand and to implement multicultural music education is crucial. It also aims at describing multicultural music education in the United States and in other countries, including the philosophical ideas, problems and opportunities behind what are stated about multiculturalism. It is hoped that this article can give more perspectives about multiculturalism in education. Keywords: multiculturalism, political debates, music education